Strategi Pengembangan Obyek Wisata Negeri Dongeng Sebagai Destinasi Wisata Unggulan Berbasis Taman Wisata Miniatur Tempoe Doeloe - Eko Adi Susilo; Lu'lu Ul Maknunah (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Tourism is one of the major assets that can generate a fairly high source of foreign exchange for the country. Therefore, every area that has certain tourism objects requires regular and sustainable tourism development so that people can take advantage of the existence of tourist destinations in the area. As with the tourism object of the Land of Fairy tales in the area of Kawedusan Ponggok Village, Blitar Regency. The design of this tour is entitled the miniature garden of the wonders of the world which is interesting to visit as a vehicle for education for children. The community can use this as a learning medium and it will have a broad impact on the people around this location to revive the economic sector. This research aims to; (1) Identifying the actual conditions of the current development aspects of the Land of Fairy Tales Tourism. (2) Identifying the influence of the tourism object of the Land of Tales as a vehicle for recreation on tourist visitors and the community around Kawedusan Ponggok Village. (3) Formulating a strategy to develop tourism objects in the Land of Tales as recreational vehicles based on the Tempoe Doeloe tourism park. The research method used by the author in this study is qualitative research and uses a descriptive analysis approach. The results of this study using SWOT analysis techniques can be concluded that the fairy tale tourism development strategy shows that the process of identifying relevant indicators is expected to be able to provide benefits in formulating a tourism development strategy for the Land of Tales in Blitar Regency. Through the formulation of a tourism strategy in a fairy tale country, it is hoped that it will be able to provide benefits to strengthening the competitive bidding position of the concepts offered. It is hoped that this will also be able to provide benefits to strengthening the economic and social aspects of the community at large.